2018
DOI: 10.46281/aijssr.v2i1.169
|View full text |Cite
|
Sign up to set email alerts
|

Poverty in Nigeria: A Social Protection Framework for the Most Vulnerable Groups of Internally Displaced Persons

Abstract: Despite strong economic growth in Nigeria, 54% of the population remains in poverty. Of significant concern is the fact that the poverty rate has doubled in the past 20 years. Internal displacement in Nigeria is a recurring and large-scale phenomenon and has affected most of the country’s 36 states. The country has seen many waves of displacement, both small and large scale, caused essentially by conflict, generalized violence, natural disasters and human rights violations all leading to loss of lives, propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
2
5
1
Order By: Relevance
“…In addition, very few of them reported access to social transfers, including food transfers. These findings corroborate previous findings49 50 on socioeconomic inequalities experienced by IDPs in Nigeria and alert to the intersection of gender, socioeconomic and HIV-related inequalities exacerbated by future health crises such as COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, very few of them reported access to social transfers, including food transfers. These findings corroborate previous findings49 50 on socioeconomic inequalities experienced by IDPs in Nigeria and alert to the intersection of gender, socioeconomic and HIV-related inequalities exacerbated by future health crises such as COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…The study lends credence to the work of Mutiso and Mutie (2018) Olanrewaju, Jeffery, Crossland and Valadez (2015), who carried out a study on access to education for OVC in Uganda, observed that 79.1% of OVC attended school within 3-year period. This particular result contradicts the finding of Okon and Ojua (2018) who maintained the percentage of OVC with regular school attendance to be a little above average (56.8%) in Cross River State and less than average (39.9%) in Ebonyi State.…”
Section: Discussioncontrasting
confidence: 86%
“…This demonstrates that most OVC in orphanages perform well academically. To buttress this point, Okon and Ojua (2018) exposed in their work that 58.6% and 66.7% of the children aged 0-9 years progressed in school over time, in Cross River and Ebonyi States, respectively, whilst 83.3% and 66.7% of children aged 10-17 years progressed in school correspondingly in Cross River and Ebonyi States. This finding contradicts the outcome of the study carried out by Pillay and Nesengani (2006) on educational challenges facing OVC.…”
Section: Discussionmentioning
confidence: 99%
“…When there is an increase in interest rates, deposit and credit rates for subsidized mortgage loans also increase so that later these interest rates will affect the fluctuations in the purchasing power of low-income people through the need to own a home. This is in line with studies [30,35,[80][81][82][83] show that the regional minimum wage affects on the purchasing power of low-income communities through the need to own a home.…”
Section: The Effect Of Regional Minimum Wage On the Purchasing Power ...supporting
confidence: 88%
“…Inflation occurs as a result of the level of the economy reaching the level of full labor unemployment and rapid economic growth [25]. Inflation occurs due to an increase in production costs [26][27][28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%